Method of correction of motive sphere for deaf schoolboys during an orientation on employments on health tourism - Baikina N.G; Pyptyuk P.F (Kharkov National Pedagogical University, 2012)
The purpose of work consists in development of method of correction of motive sphere and linguistic development running on speed and endurance for deaf schoolboys which are engaged in health tourism. In an experiment deaf schoolboys took part 12-14 years. The sizes of latent period of reaction are set on a light signal and change in the indexes of nervous muscle vehicle. Bases of preparation of schoolboys are recommended on tactic of orientation on employments by health tourism. The features of speeding up and endurance are selected for deaf and hearings schoolboys on employments on an orientation. It is set that the correction of motive sphere must be carried out on the basis of running preparation - on speed and endurance. It is thus necessary to extend and choose the volume of initial verbal information - verbal, writing, haptic, gesticulation. It is marked about importance of introduction of sporting technicals in the process of implementation at run, multiple to repeat verbal information about logic of inversely connect actions of student. It is set that playing, repeated, competition and circular methods must be combined with verbal components in all of accessible forms. Also, in combination with a show and operative correction of their activity.